Science Learning E-Module for Fourth Grade Elementary School Students - Oni Rianti; Simamora, Alexander Hamonangan (Universitas Pendidikan Ganesha, 2023)
The background to this research development is the lack of use or provision of teaching materials or learning resources to support the science learning process and to improve student learning outcomes. Lack of increased student learning outcomes due to the lack of learning resources used. Therefore this study aims to development of e-modules with a natural science contextual approach in order to improve learning outcomes. This type of research uses the ADDIE model development (analyze, design, development, implementation, evaluation). Data collection methods used are questionnaires, pre-test and post-test. Data analysis techniques using descriptive qualitative analysis, quantitative and inferential statistics. The results showed that the developed e-module is valid with the validity results obtained from the review of learning content experts by 97% with very good predicate, 90.90% learning media expert with very good predicate, 91.66% learning design expert with very good predicate good, individual trials 95.51% with very good predicate, small group trials 96.15% with very good predicates and field tests 95.74% with very good predicates. Then the results of the effectiveness of developing e-modules with a contextual approach to science subjects showed that there were differences in student learning outcomes after and before using the learning e-module.